The future of the Romanian rural household from the perspective of agricultural censuses - Valentin Mihai Bohatereţ; Ioan Sebastian Brumă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The development of agriculture in nowadays circumstances cannot be merely assessed from the perspective of agriculture as a main branch of national economy, but further from a social point of view which is highly significant as it represents the traditional small farm households which provide the basic necessaries for the rural population as well as the usability implication of over 55% from the agricultural area of the country. On the whole, by agricultural exploitation there is the general tendency of considering its commercial aspect only, perfectly justifiable in the case of agricultural exploitations with a legal, juridical character, but there is also to be regarded the social aspect of agricultural exploitation without a juridical status, which is largely representative for the small farm households. In the period of time between the 2 General Censuses (2002 and 2010) the agricultural exploitations without a legal, juridical status diminshed by 13.6%, while the agricultural area used diminshed by 3.3% only, leaving over 7.5 million agricultural area as responsability for these exploitations.
Keywords: 330; rural/ small farm household; agricultural exploitation without a legal/ juridical status; the size of the agricultural exploitation; the agricultural area used